2017
DOI: 10.1177/0023677217708807
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory animal science course in Switzerland: participants’ points of view and implications for organizers

Abstract: Switzerland has implemented a mandatory training in laboratory animal science since 1999; however a comprehensive assessment of its effects has never been undertaken so far. The results from the analysis of participants in the Swiss Federation of European Laboratory Animal Science Associations (FELASA) Category B compulsory courses in laboratory animal science run in 2010, 2012, 2014 and 2016 showed that the participants fully appreciated all elements of the course. The use of live animals during the course wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Research institutions have to make such training available frequently in order to enable new researchers to get started with their work. 15 Students on the other hand will have to make time for training in busy professional schedules. Indeed, e-learning is already considered the key to meet training requirements in a related situation, training of veterinary professionals, allowing users to manage their learning through the optimization of time availability and overcoming spatial constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Research institutions have to make such training available frequently in order to enable new researchers to get started with their work. 15 Students on the other hand will have to make time for training in busy professional schedules. Indeed, e-learning is already considered the key to meet training requirements in a related situation, training of veterinary professionals, allowing users to manage their learning through the optimization of time availability and overcoming spatial constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, analysis of course evaluations [ 101 ] and surveys conducted with participants of LAS courses [ 102 ] concerning their attitude toward LAS courses, i.e., the use of live animals for training or the evaluation of particular course aspects revealed that the respondents considered practice of handling and routine procedures, including practice on a live animal, as a very important part in preparatory training. Therefore, simulator-based training may be considered a meaningful supplement in the sense of the 3R principle for LAS training which, however, should be further developed in future.…”
Section: Discussionmentioning
confidence: 99%
“…This requires clear communication of the course goals and the use of live animals in hands-on components. 16 Second, it is difficult to arrange a course that fits with students’ conflicting schedules in different programmes but offering it fully online or in a blended version are equally beneficial alternatives. 17…”
Section: Introductionmentioning
confidence: 99%
“…Online options for LAS courses are considered useful by course providers and students because they make the content accessible with flexible timing options. 17 They also contribute to the sustainability and availability of the courses in response to the demands of an increasing number of researchers 16 and have the potential to train researchers abroad. It is expected that the current pandemic will boost the number of online or blended courses.…”
Section: Introductionmentioning
confidence: 99%